Description of a new Neotropical species of Mathevotaenia (Cestoda: Anoplocephalidae), a parasite of the Virginia opossum Didelphis virginiana - Coronado-Morones, Diana; Alonso Panti-May, Jesus; Torres-Carrera, Gerardo; Garcia-Prieto, Luis (Folia parasitologica, 2025)
The cestodes of the genus Mathevotaenia Akhumyan, 1946, are parasites of mammals, although some species also occur in reptiles. The genus comprises 61 species distributed worldwide, 25 of which occur in the American continent. During a collection of mammals in Yucatán, Mexico, six specimens of a cestode belonging to Mathevotaenia were found in the Virginia opossum Didelphis virginiana Kerr. The aim of this study is to morphologically describe these specimens, which represent a new species, and to evaluate their phylogenetic position within the Anoplocephalidae, based on cox1, 28S rDNA and ITS sequences. The new species is distinguished from its congeners by the combination of the following characters: a high number of ovarian lobes, comparable only with Mathevotaenia wallacei (Chandler, 1952), and a body proper size similar to that of M. diminuta Navone, 1988, M. oklahomensis (Peery, 1939) and M. brasiliensis Kugi et Sawada, 1970.
Keywords: Cestoda; DNA helmintů; DNA, Helminth; cestodózy; fylogeneze; Phylogeny; Linstowiinae; RNA ribozomální 28S; marsupials; Animals; ženské pohlaví; Mexico; zvířata; tapeworms; Didelphis; phylogeny; Female; RNA, Ribosomal, 28S; Cestode Infections; Mexiko